Are adolescents’ physical activity and body-related factors associated with medically attended injuries? - Karchynskaya, Viktoryia; Kopcakova, Jaroslava; Madarasova Geckova, Andrea; Bakalár, Peter; de Winter, Andrea F.; Reijneveld, Sijmen A. (Frontiers in Pediatrics, 2022)
Background: Injuries are the major cause of disability and death during adolescence, representing a significant public health burden among youth. Body-related factors such as body composition and cardiovascular fitness (CVF) may affect adolescents’ vulnerability to injuries. As evidence is lacking, we aimed to explore the associations of medically attended injuries with adolescents’ physical activity (PA) and body-related factors, and whether these associations are modified by age, gender and family affluence. Methods: We used data on 888 11- to 15-year-old adolescents (mean age=13.5, 56% boys) from the Health Behaviour in School-aged Children study conducted in 2018 in Slovakia. We used binary logistic regression analysis to assess the association of medically attended injuries with adolescents’ PA and body-related factors (body composition, CVF), considering age, gender and family affluence. Results: Adolescents were more likely to report medically attended injuries if they were physically very active (odds ratio/confidence interval OR/CI:2.76/1.83–4.15) or active (OR/CI:1.91/1.27–2.87) rather than inactive. Body-related factors were not associated with medically attended injuries among adolescents. Moreover, age, gender and family affluence did not modify the association of medically attended injuries with adolescents’ PA and body-related factors. The only exception was the modifying effect of gender: the association of medically attended injuries with being very active was stronger in boys (OR/CI: 3.04/1.32–6.99). Conclusion: Very physically active adolescent boys are the most vulnerable group of adolescents in terms of injuries. PA promotion programmes should further consider gender-specific strategies aimed at preventing injuries.